(untitled) (Bangladesh Journal of Otorhinolaryngology, 2023)
Background: Incidence of laryngeal cancer still high among the upper aerodigestive tract. 85–95% of these laryngeal cancer is squamous cell carcinoma. Locally advanced laryngeal cancer metastasize more. Supraglottic cancers have the highest prevalence of regional metastases among laryngeal cancers. Objectives: To evaluate the frequency of regional metastasis in supraglottic carcinoma of larynx. Methods: This cross-sectional study was conducted including 40 patients with supraglottic Carcinoma of Larynx over a period of six months from June to November 2014 in the ENT and Head Neck Surgery department of Rajshahi Medical College Hospital, Rajshahi. Those with glottic carcinoma, subglottic carcinoma, hypopharyngeal carcinoma, metastatic neck node without any primary site (Occult primary) were excluded from the study. FNAC from neck node was done in patients with palpable neck node. Results: Most of the patients 19 (47.5%) was in age group 50-60 years with mean age 54.5±13.2 years. Most of the patients present with more than one symptom & the commonest presenting symptoms was cough and irritation 35(87.5%) followed by dysphagia 26(65%) and change of voice 24(60%). A good number of patients, 16(40%) was presented with neck swelling. Among 40 patients, 16(40%) had their regional lymph nodes involved. Level-II lymph nodes were involved in higher number of cases 10(62.5%). Nodes in early stage of involvement were found in most cases 9(56.5%). Homolateral involvement of nodes was found in most cases 13(81.3%).Most of the supraglottic growths 22(55.0%) was exophytic in appearance. The common site of supraglottic carcinoma in this study was aryepiglottic fold and arytenoids 20(50.0%). Among the patients, 31(77.5%) had T2 tumours. Amon them, 16(40%) were in stage-III followed by stage-II 10(25%). Conclusion: Regional metastasis is a very useful prognostic indicator. Supraglottis is rich in lymphatic drainage and a high proportion of these tumors spread to lymph nodes. Bangladesh J Otorhinolaryngol 2022; 28(2): 180-185